Pertanggungjawaban Notaris Sebagai Pejabat Lelang Kelas II - Anggy Atmadi Karunia; Anang Husni; Sudiarto - (Fakultas Hukum Universitas Mataram, 2017)
The purpose of this study is to know the form of notary responsibility as an auction official class II and to know the auction mechanism by auction official class II and to know the form of law protection for notary as auction official class II. this study conducted by juridical normative methods which is a legal writing by looking norms and relevant legal theory is based on the existing literature. The result of this research is, 1) the form of responsibility from Notary who served as auction official class II. Is administration sanction if he/she break the regulation of notary and also Asked for compensation for Harm the parties because his deed or he/she can be criminalized if he/she conduct criminal act. 2)the auction mechanism by auction official class II is divided into three step, the first step is preparation step, second is auction implementation and the last step is the completion of auction deed by auction offial class II. 3)the form of protection which honorary council can gave to notary who served as auction official class II is same as well as a common notary like summoning by investigator, public prosecutor and judge and And taking photocopies of deed from notary safekeeping.